1997
DOI: 10.1046/j.1365-2117.1997.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

New palaeogeographic and lake‐level reconstructions of Lake Tanganyika: implications for tectonic, climatic and biological evolution in a rift lake

Abstract: Palaeogeographic and lake‐level reconstructions provide powerful tools for evaluating competing scenarios of biotic, climatic and geological evolution within a lake basin. Here we present new reconstructions for the northern Lake Tanganyika subbasins, based on reflection seismic, core and outcrop data. Reflection seismic radiocarbon method (RSRM) age estimates provide a chronological model for these reconstructions, against which yet to be obtained age dates based on core samples can be compared. A complex his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
178
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(185 citation statements)
references
References 3 publications
7
178
0
Order By: Relevance
“…As predicted by the epi-transposon hypothesis, analysis of 75 SINE loci indicates that this haplochromine lineage has experienced repeated bouts of cichlid-specific SINE insertions followed by extensive radiations within each lake. (108) Moreover, geological evidence of aridification in East Africa 2.5-3 Mya (94) and extreme lake level fluctuations of several hundreds of meters over the last 1.1 My (109) is consistent with epigenetic regulation of cichlid TEs breaking down in response to environmentally induced physiological stress.…”
Section: Te Expansions and Adaptive Radiationsmentioning
confidence: 80%
“…As predicted by the epi-transposon hypothesis, analysis of 75 SINE loci indicates that this haplochromine lineage has experienced repeated bouts of cichlid-specific SINE insertions followed by extensive radiations within each lake. (108) Moreover, geological evidence of aridification in East Africa 2.5-3 Mya (94) and extreme lake level fluctuations of several hundreds of meters over the last 1.1 My (109) is consistent with epigenetic regulation of cichlid TEs breaking down in response to environmentally induced physiological stress.…”
Section: Te Expansions and Adaptive Radiationsmentioning
confidence: 80%
“…Prior attempts to date major diversification events within the cichlids (47,(51)(52)(53) have been based on the timing of the post-LGM lake-level rise and on much older, weakly constrained outcrop (54) or seismic data (55,56) from the two lakes. The megadrought low-stand demonstrated here for Lake Malawi provides a much more robust constraint on genetic divergence within the cichlid phylogeny, implying rates of evolution four to eight times slower than those that assume a major role for the LGM in Lake Malawi speciation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested mitochondrial introgression, sometimes on a small scale between presently allopatric populations, sometimes on a large-scale producing true hybrid populations, at various time points in the evolutionary history of the genus Tropheus. Most of these events of population displacement were triggered by lake level fluctuations, which extended to a few hundred meters below present level (Lezzar et al, 1996;Cohen et al, 1997;Scholz et al, 2003;McGlue et al, 2008). While the effect is widely seen in population genetic studies on various Lake Tanganyika cichlid species (Verheyen et al, 1996;Rüber et al, 1999Rüber et al, , 2001Duftner et al, 2006;Koblmüller et al, 2007Koblmüller et al, , 2009Koblmüller et al, , 2011Sefc et al, 2007;Nevado et al, 2013;Van Steenberge et al, 2015), studies specifically testing for the impact of Pleistocene water level fluctuations are scarce (Koblmüller et al, 2011;Winkelmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%